Multiple basal cell carcinomas in a patient with myotonic dystrophy type 1. Issue 3 (8th March 2019) - Feng, Jessica; LaChance, Avery; Sinclair, David A; Asgari, Maryam M
Abstract : A man in his early 60s with myotonic dystrophy type 1 (DM1) and an extensive history of non-melanoma skin cancer presented with multiple pearly, erythematous papules on his face, head, trunk and extremities, clinically consistent with basal cell carcinoma (BCC). Due to the numerous BCC and history of multiple and early-onset BCC, examination was concerning for a hereditary BCC syndrome. Subsequent histopathology confirmed BCC. Genetic testing was negative for basal cell nevus syndrome and clinical findings were inconsistent with other known hereditary BCC syndromes. There have been reports of an association between DM1 and BCC, however, it is not well known among clinicians. We hope to raise awareness among clinicians about this association.